Genetic and phenotypic differentiation of an Andean intermediate altitude population - Eichstaedt, Christina; Antão, Tiago; Cardona, Alexia; Pagani, Luca; Kivisild, Toomas; Mormina, Maru (Physiological reports, 2015)
Highland populations living permanently under hypobaric hypoxia have been subject of extensive research because of the relevance of their physiological adaptations for the understanding of human health and disease. In this context, what is considered high altitude is a matter of interpretation and while the adaptive processes at high altitude (above 3000 m) are well documented, the effects of moderate altitude (below 3000 m) on the phenotype are less well established. In this study, we compare physiological and anthropometric characteristics as well as genetic variations in two Andean populations: the Calchaquíes (2300 m) and neighboring Collas (3500 m). We compare their phenotype and genotype to the sea-level Wichí population. We measured physiological (heart rate, oxygen saturation, respiration rate, and lung function) as well as anthropometric traits (height, sitting height, weight, forearm, and tibia length). We conducted genome-wide genotyping on a subset of the sample (n = 74) and performed various scans for positive selection. At the phenotypic level (n = 179), increased lung capacity stood out in both Andean groups, whereas a growth reduction in distal limbs was only observed at high altitude. At the genome level, Calchaquíes revealed strong signals around PRKG1, suggesting that the nitric oxide pathway may be a target of selection. PRKG1 was highlighted by one of four selection tests among the top five genes using the population branch statistic. Selection tests results of Collas were reported previously. Overall, our study shows that some phenotypic and genetic differentiation occurs at intermediate altitude in response to moderate lifelong selection pressures.